News Media Writing - Ricky W. Telg (EDIS)
Knowing how to write in a news media style is important not only for an organization’s reporters, but also for its members. This 2-page fact sheet provides an overview of news writing for print, television, and radio to help you better communicate news about what is going on in your organization. Written by Ricky Telg, and published by the UF Department of Agricultural Education and Communication, January 2015.